Survey archeology : How 'evil' is depicted in comic books - Gomes, Marcelo Bolshaw (9 Arte (São Paulo), 2019)
The present text problematizes the symbolic content and the representation of evil through the villains of the two main narrative universes of comics (DC Comics and Marvel). Through the notion of Greimas's Anti-subject, each character is analyzed and how it fits into his narrative universe. The goal is, from an archeology of antagonists, to sketch an anatomy of narrative evil in its various versions.